Shaping battlefield with emerging technologies - Rachna Dua (National Geographical Journal of India, 2023)
The past decade has seen a disturbing trend of hyper-nationalism and a tectonic shift in global hierarchies from a unipolar to a multipolar world, with China challenging the USA's pole position. Despite the troubled history of the twentieth century and the past two and a half decades in particular, increased interdependence and the spread of technology are the powerful forces that will shape the future global scenario. This review article explores the emerging technologies that will shape the future battlefield. It examines the future battlefield environments and capability enhancement with global and regional imperatives. It also identifies India's interests, threats, and military imperatives with 'Atmanirbhar Bharat' in defence. The chosen theme holds significant relevance for global stability in general and India's interests in particular.